2019 IEEE/CVF International Conference on Computer Vision (ICCV) 2019
DOI: 10.1109/iccv.2019.00039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Robustness of Deep Image Super-Resolution Against Adversarial Attacks

Abstract: Single-image super-resolution aims to generate a highresolution version of a low-resolution image, which serves as an essential component in many computer vision applications. This paper investigates the robustness of deep learning-based super-resolution methods against adversarial attacks, which can significantly deteriorate the superresolved images without noticeable distortion in the attacked low-resolution images. It is demonstrated that stateof-the-art deep super-resolution methods are highly vulnerable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…clean inputs [20] and have shown to fail to be robust to many adversarial attacks [21], [34]. Instead of attempting to modify inputs, RAILS evolves a statistical population of clones of the input, resulting in enhancing resilience to attacks.…”
Section: A Related Workmentioning
confidence: 99%
“…clean inputs [20] and have shown to fail to be robust to many adversarial attacks [21], [34]. Instead of attempting to modify inputs, RAILS evolves a statistical population of clones of the input, resulting in enhancing resilience to attacks.…”
Section: A Related Workmentioning
confidence: 99%
“…3 Proposed Method 3.1 Motivation (Choi et al 2019) showed that SISR networks perform poorly on unseen degradations. In order to train a robust facial SISR network for real-world application, we would therefore need a dataset with paired examples of degraded LR and clean HR images.…”
Section: Adversarial Robustnessmentioning
confidence: 99%
“…In addition, when one needs to use the models to build an extension of the super-resolution task, it is necessary to implement it repeatedly for all the frameworks. Examples of the extension include image classification using super-resolved images [12] and robustness analysis of superresolution against adversarial perturbations [13].…”
Section: Models With Different Frameworkmentioning
confidence: 99%
“…In addition, the provided superresolution models can be used to thoroughly analyze their intermediate processes by computing the features and gradients. One example use case is to examine the robustness of the super-resolution models by adding a small perturbation to a given input image, which erroneously deteriorates the super-resolved outputs [13]. Therefore, SRZoo can be employed as a testbed to analyze and refine the state-of-the-art deep learning-based super-resolution methods.…”
Section: Extension To Advanced Topicsmentioning
confidence: 99%